142 UMP LOs makes it a mission to send students home - Nur Sa’adatul Afzan, Jusoh (2020)
Kuantan, 20 May 2020 - The fact that staff members who check on students so that only healthy people are allowed to board buses and regularly check travel documents and regularly contact the Royal Malaysian Police (PDRM) raises questions as to who they are.